Consortium blockchain‐enabled access control mechanism in edge computing based generic Internet of Things environment. Issue 6 (4th June 2020) - Saha, Sourav; Chattaraj, Durbadal; Bera, Basudeb; Kumar Das, Ashok
Abstract: This article introduces a new consortium blockchain‐enabled access control scheme in edge computing based generic Internet of Things environment (called CBACS‐EIoT), where the mutual authentication among the IoT smart devices and the gateway node(s), and also among the gateway node(s) and respective edge server(s) occur. In addition, key management phase is executed among the edge server(s) and associated cloud server(s). Using the established secret keys, the entities in the network communicate securely. The data gathered securely by the gateway nodes are then used to form various types of blocks (private, public, or consortium) at the edge server(s) based on application types in the generic IoT environment. The created blocks are mined by the edge servers in order to add them in the blockchain center. A detailed security analysis including the formal security has revealed that the proposed CBACS‐EIoT is robust against various potential attacks needed in the IoT environment. To further strengthen the security, the simulation‐based formal security verification on CBACS‐EIoT has been carried out to exhibit that CBACS‐EIoT is secure against passive and active attacks. Finally, a meticulous comparative performance analysis shows that CBACS‐EIoT offers superior security and supports more functionality features, and also provides less communication and computational overheads compared with existing relevant schemes. Abstract : Blockchain‐based network model for generic IoT network.